Selection of Fungicides for Control of Eucalypt Powdery Mildew - Bizi, Rafaela Mazur (2011)
The objective of this study was to find effective fungicides against eucalypt powdery mildew. Fungicides tested were chlorothalonil, fenarimol, sulfur, tebuconazole, propiconazole, benzothiazole, pyraclostrobin + epoxiconazole and triadimenol. These fungicides were sprayed on Eucalyptus benthamii seedlings in a greenhouse infested with powdery mildew. Severity was evaluated at 9, 16, 23, 30 and 37 days after spraying, classifying symptoms observed with a scale 0 (symptoms absent) to 4 (strong symptoms). Best treatments were obtained with pyraclostrobin + epoxiconazole, propiconazole + trifloxystrobin and triadimenol, with an infection index average of 0.39, 0.63 and 1.01, respectively.